Selected Factors Affecting the Learning Organization of Nursing in Wing Hospitals - Prathum, Pornpawee; Juntachum , Wanchanok (Medical Journal of Sakon Nakhon Hospital, 2024)
This research was a descriptive study aimed at investigating and analyzing the factors that affect the learning organizations of nursing in Wing hospitals. The samples were 140 professional and technical nurses who have actively been working in Wing hospitals for a minimum of 1 year. The research tool used was a questionnaire developed by the researcher, which included the assessment of system establishing to collect and share knowledge, connecting the organization to its environment, leadership for learning support and becoming the learning organization of nursing. The questionnaires’ content validity was verified by six qualified experts. The reliability tested by the Cronbach’s alpha coefficient were 0.74, 0.85, 0.90 and 0.91, respectively. The total of 111 questionnaires were returned, accounting for 79.29 percent. The data were analyzed using the frequency distribution statistics, percentages, mean, standard deviation, Pearson's correlation coefficient and stepwise multiple regression analysis. The study found that the overall level of being the learning organization of nursing in Wing hospitals was at a high level (= 3.60, S.D. = 0.68) and the variables that jointly predicted the perception of being the learning organization of nursing statistically significant at the 0.01 level were leadership for learning support, connecting the organization to its environment, and system establishing to collect and share knowledge. These variables can jointly predict the perception of being the learning organization of nursing in Wing hospitals by 82.4 percent (R2 = 0.824).